Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1152/japplphysiol.00670.2007
|View full text |Cite
|
Sign up to set email alerts
|

Collagen, cross-linking, and advanced glycation end products in aging human skeletal muscle

Abstract: We examined intramuscular endomysial collagen, cross-linking, and advanced glycation end products, as well as the general and contractile protein concentration of 20 young (25 +/- 3 yr) and 22 old (78 +/- 6 yr, range: 70-93 yr) sedentary men and women to better understand the underlying basis of changes in skeletal muscle mass and function that occur with aging. The old individuals had an impaired ability (increased time) (P < 0.05) to climb stairs (80%), rise from a chair (56%), and walk (44%), as well as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
276
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(295 citation statements)
references
References 50 publications
6
276
2
1
Order By: Relevance
“…Transverse aponeurosis modulus increased from 188.5± 24.2 MPa (N=5) in young rats to 328.0±48.3 MPa (N=5) in old rats (Table 1). The observed change in transverse aponeurosis stiffness is likely to be a result of increases in the amount and cross-linking of collagen with age (Alnaqeeb et al, 1984;Bailey, 2001;Haus et al, 2007).…”
Section: Connective Tissue Propertiesmentioning
confidence: 99%
“…Transverse aponeurosis modulus increased from 188.5± 24.2 MPa (N=5) in young rats to 328.0±48.3 MPa (N=5) in old rats (Table 1). The observed change in transverse aponeurosis stiffness is likely to be a result of increases in the amount and cross-linking of collagen with age (Alnaqeeb et al, 1984;Bailey, 2001;Haus et al, 2007).…”
Section: Connective Tissue Propertiesmentioning
confidence: 99%
“…We also determined the AGE accumulation in skin using a noninvasive method based on autofluorescence (AGE reader; Meerwaldt et al 2004). It has been shown that the difference between young and older individuals in AGE cross-link density in collagen is twofold in skin (Verzijl et al 2000) and skeletal muscle (Haus et al 2007), fivefold in bone (Saito et al 1997), sevenfold in tendon (Couppe et al 2009), ninefold in ligaments (Chen et al 2000), and 33-fold in cartilage (Verzijl et al 2000) demonstrating marked age-related differences in tissue-specific turnover. The present data showed 45 % higher values in skin with aging, but also 11 % lower values by training, indicating that routinerunning reduced the age-related AGE accumulation in skin.…”
Section: Youngmentioning
confidence: 99%
“…AGE cross-links accumulate with age in long-lived proteins, such as collagen, resulting in markedly higher concentrations in older than in younger individuals (Chen et al 2000;DeGroot et al 2001;Haus et al 2007;Bank et al 1999;Suzuki et al 2008). The accumulation appears to be accelerated with age-related chronic diseases such as diabetes (Dyer et al 1993;Vogt et al 1982) and is believed to influence the function of several tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Following freeze drying, each sample was homogenized in 40 volumes of cold homogenizing buffer (250 mM sucrose, 100 mM potassium chloride, 20 mM imidazole, and 5 mM EDTA; pH 6.8) in a ground-glass homogenizer (Radnoti Glass Technology, Monrovia, CA) (10). An aliquot of each homogenate was measured for protein concentration using the bicinchoninic acid assay (Sigma) with bovine serum albumin used as the protein standard (20,44). The amount of protein and water in each sample was normalized to muscle wet weight.…”
Section: Muscle Protein and Water Quantificationmentioning
confidence: 99%